A study on the development of assay systems for the determination of certain antipsychotic phenothiazines and benzodiazepines - Uebel, Reinhard Andreas,1958- (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD (Med.)) -- University of Stellenbosch, 1993.